2016
DOI: 10.1016/j.cej.2015.12.105
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of dichloromethane under non-oxidative conditions in a dielectric barrier discharge reactor and characterisation of the resultant polymer

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Reaction of dichloromethane under non-oxidative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The Cl-H bonding energy of CH 2 Cl 2 is 4.28 eV and is lower than the energy of metastable Ar (11.55 eV) produced by electron impact, as shown in reaction ( 9) [99]. Therefore, CH 2 Cl 2 is also possibly decomposed by Penning ionization by the energy transfer collision of metastable Ar (Ar*) as shown in the following reactions: [99,100].…”
Section: Decomposition Of Persistent Organic Pollutantsmentioning
confidence: 99%
“…The Cl-H bonding energy of CH 2 Cl 2 is 4.28 eV and is lower than the energy of metastable Ar (11.55 eV) produced by electron impact, as shown in reaction ( 9) [99]. Therefore, CH 2 Cl 2 is also possibly decomposed by Penning ionization by the energy transfer collision of metastable Ar (Ar*) as shown in the following reactions: [99,100].…”
Section: Decomposition Of Persistent Organic Pollutantsmentioning
confidence: 99%
“…It has been reported that 99.9% of HFC-134a and CF 4 can be decomposed by the use of plasma technology [12]. Moreover, undesirable byproducts, such as COF 2 have been reported to be controlled, and it is considered to be proficient in treating HFC-134a over a wide range of initial concentrations [13][14][15][16]. However, the high initial operating costs coupled with low energy efficiency restrain the dominance of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding energy of Cl-H of CH 2 Cl 2 is 4.28 eV, and is lower than the energy of Ar metastable (11.54 eV) 28). Therefore, CH 2 Cl 2 is also possibly decomposed by the Penning ionization by the energy transfer collision of Ar metastable (Ar*) as shown in following reactions;28,29) …”
mentioning
confidence: 99%